VD_FINDINFO AM 16/10 - 51/2011 vom 27. Juni 2011 - VD Tribunal cantonal (2011)
AFFECTION DENTAIRE, MÉDECINE DENTAIRE | 25 al. 1 LAMal, 27 LAMal, 31 al. 1 LAMal, 33 al. 2 LAMal, 33 al. 5 LAMal, 3 LPGA, 19 OPAS, 19a OPAS